JIG AND FIXTURE PENGELASAN SUDUT SIKU UKURAN LEBAR PROFIL (3 - 60 mm) DI JURUSAN TEKNIK MESIN POLITEKNIK NEGERI MALANG - Marthania Putri Indrayati; Rafik Djoenaidi; Andri Setiawan (Polinema Press, Politeknik Negeri Malang, 2021)
The resulting angle deviation is the result of improper welding methods, in addition, there is also a distortion factor in the workpiece during the SMAW welding process at the workshop in the Department of Mechanical Engineering, State Polytechnic of Malang.The purpose of making this tool is to facilitate and provide time efficiency in the welding process, it is necessary to manufacture jig and fixture tools in the angle welding process. The way the angle welding jig and fixture works is by gripping the workpiece to be welded in a plane that forms an angle so that the object to be welded will follow the angled plane.